1998
DOI: 10.1088/0026-1394/35/4/35
|View full text |Cite
|
Sign up to set email alerts
|

A new FEL-type quartz-halogen lamp as an improved standard of spectral irradiance

Abstract: Based on extensive investigations of almost 100 high-power quartz-halogen lamps covering thirteen different types, seven different manufacturers and different batches with a total operating time of about 27000 h, a new type of lamp (1000 W T6 modified FEL-type lamp, Osram Sylvania Inc.) has been selected and its operating conditions have been optimized. This lamp, which after seasoning is about ten times more stable than the best lamps used before, is recommended as a reference and transfer standard of spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 3 publications
(5 reference statements)
1
21
0
Order By: Relevance
“…Experience showed that the total lifetime of FEL-type lamps can be extended to 500 h if the lamps are aged carefully, are prevented from shock and vibration and are not operated over allowed nominal power [17,18]. Three FEL-type lamps were chosen for use as irradiance standards.…”
Section: Preparations and Testing Of The Lampsmentioning
confidence: 99%
“…Experience showed that the total lifetime of FEL-type lamps can be extended to 500 h if the lamps are aged carefully, are prevented from shock and vibration and are not operated over allowed nominal power [17,18]. Three FEL-type lamps were chosen for use as irradiance standards.…”
Section: Preparations and Testing Of The Lampsmentioning
confidence: 99%
“…As a result, appropriate working standards in terms of achievable irradiance levels, spectral power distribution and handling simplicity are needed. Typical transfer standards presently used for the dissemination of the spectral irradiance unit are based either on FEL-type quartz-halogen lamps (250 nm to 2500 nm) or on deuterium lamps (200 nm to 400 nm) [1,2]. In fact, such transfer standards are mostly not able to fulfil all of the above-mentioned conditions in the UV region.…”
Section: Introductionmentioning
confidence: 99%
“…Realization of the spectral irradiance unit is based on the comparison method [2], where the value of spectral responsivity is transferred to filter radiometers and a spectroradiometer (used as a wavelength tuneable-filter radiometer). A filter radiometer is then used for spectral irradiance unit realization, whereas a spectroradiometer is used for derivation of the relative spectral irradiance of the FEL 1000 lamp [3].…”
Section: Introductionmentioning
confidence: 99%